Propuesta gráfica de arte digital, con una visión irónica de las expresiones corporales en la fotografía dentro de la sociedad lojana - Velepucha Gualan, Danny Antonio (2019)
The present research entitled Graphic proposal of digital art, with an ironic vision of body expressions in photography within the lojana society, develops a theoreticalpractical work, which investigates digital art, its artistic and aesthetic foundation, allowing to explore the multiple expressive potentials offered by technologies, particular creative processes in various fields with interdisciplinary projection. For the process, the observation is proposed for experimentation, the deductive - inductive method that allows greater knowledge about theories, positions, artistic and aesthetic criteria to support the proposal of digital art along with the line of photography. With all these elements, it was possible to understand and analyze how digital art allows to approach the development of personal artistic visions and links with other branches such as photography, providing a number of possibilities to create and disseminate it; works inspired by showing the ironic message through body expressions.